Queervertising: ¿es la publicidad gay-friendly? - Iglesias-Sánchez, Patricia Pilar; Jambrino-Maldonado, Carmen; Fernández-Díaz, Elena; De-las-Heras-Pedrosa, Carlos (My University, 2023)
This study analyzes how advertising and society interact and evolve in parallel, with advertising trying to balance more traditional representations with integration, which can influence social change. In this case, the analysis focuses on the homosexual community. A content analysis of audiovisual advertising in Spain from the 1960s to 2021 is carried out in addition to a review of historical milestones and legislation. The results show the transformation of advertising, showing the transition from total invisibility of gays and lesbians in the 60s to a respectful integration today. Queervertising is proposed as a new theoretical concept as a result of the identification of gender and sexual diversity in advertising over time. Although even today they are still not disruptive or excessively explicit, to avoid certain rejection by audiences.
Keywords: Minorías sexuales; Publicidad; LGTB; Queervertising; Diversidad sexual; Género